Analisis Hasil Belajar Sosiologi antara Peserta Didik yang Bekerja dan Tidak Bekerja di Kelas XI IPS SMAK Abdi Wacana Pontianak - Veraliana Sendy; Yohanes Bahari; Nining Ismiyani (ISLAMIKA, 2023)
The purpose of this study was directed to find out the learning outcomes of class XI IPS students at SMAK Abdi Wacana Pontianak who are working and who are not working. A strategy known as descriptive qualitative method is used in this study. In gathering information, the techniques implemented were observation, interviews, and documentation, then the tools used in collecting data were observation guides, interview guides, and media documentation. In analyzing the data, it is done interactively and continuously using data reduction or grouping techniques, then presenting the data, and finally concluding the results of the analysis based on every fact found. The presentation of the results of data analysis in this study was carried out descriptively on the basis of the findings obtained from 16 informants. The results of this study show that the work of students is not an influence on learning outcomes, but instead a stronger influence can be seen from the self-motivation of each student.